WRITERS' UNION IN BUKHARA - Akhmadov Amonkeldi Hasanovich (Western European Studies, 2024)
The article provides the latest information based on archival materials about the reorganization of the Bukhara branch of the Writers' Union of Uzbekistan and its activities in the early years, its significance in the history of the literary environment of Bukhara, as well as about literary associations and circles established in the region
Keywords: History of the literary environment of Bukhara; Writers' Union; Toshpulat Hamidov; Pedagogical Institute